PENGARUH MANAJEMEN LABA DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (STUDI EMPRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015) - Hijah Maisyarah; Hj. Maslichah Hj. Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2017)
The purpose of this study is to analyze the effect of earnings management and financial performance on the value of companies listed in Indonesia Stock Exchange (BEI) period 2013-2015. Sampling technique used purposive sampling method, which is used as sample in this study as many as 40 Manufacturing companies listed in Indonesia Stock Exchange. After testing the data normality there are 20 outliers with three years of observation, so the sample can be managed only 60 companies. The data used in this research is secondary data. Analysis of research data using multiple linear regression with the help of SPSS 23 program. The results of this analysis indicate that the variable of earnings management has a significant positive correlation to firm value, while the variable of financial performance have a significant negative effect to firm value.